THE RELATIONSHIP BETWEEN PHYSICAL DEVELOPMENT INDICATORS AND THE POWER OF ANAEROBIC ENERGY SUPPLY PROCESSES IN WOMEN OF DIFFERENT SOMATOTYPES - Miroshnichenko, V. M.; Оnyshchuk V. Eu.; Riabchenko, V. G. (Rehabilitation and Recreation, 2025)
Anaerobic energy supply plays a key role during physical efforts of maximal and submaximal intensity. Therefore, studying the factors that influence the ability to perform physical activity through anaerobic metabolism is relevant. It has been proven that individuals of different morphological types differ in both aerobic and anaerobic performance of the body, as well as in the manifestation of physical qualities. Active research is being conducted to identify relationships between physical development indicators and functional fitness parameters in athletes. We did not find data in the literature regarding the correlations between physical development indicators and anaerobic performance indicators in women aged 25–35 with different somatotypes. The aim of this study is to establish the specifics influence of body weight, height, fat and muscle components on anaerobic performance in women aged 25–35 with different somatotypes. The power of anaerobic alactic energy supply processes was determined using the 10-second Wingate test. The power of anaerobic lactic energy supply processes was determined by using the 30-second Wingate test. It was established that the degree of correlation between indicators of physical development and indicators of anaerobic performance of the body in representatives of different somatotypes differs significantly. A high degree of correlation was found between the absolute values of WAnT 10, WAnT 30, and body mass, height, and BMI in women with ectomorphic and balanced somatotypes. For relative values, a high correlation was found only in women with a balanced somatotype – between WAnT 30 and body mass. Conclusions. Anaerobic performance indicators in women with endomorphic and endomesomorphic somatotypes show significantly weaker correlations with physical development indicators compared to women with ectomorphic and balanced somatotypes. Body mass, height, and BMI may serve as predictors of high anaerobic performance in women with balanced and ectomorphic somatotypes. The percentages of body fat and muscle do not have a significant impact on the anaerobic capacity of women across all somatotypes.